Online Learning in Social Adaptation Perspective - Pardamean Daulay; M Chairul Basrun Umanailo; Aulia Nursyifa (HUMAYA Jurnal Hukum Humaniora Masyarakat dan Budaya, 2021)
The trend of online learning is growing. Through the Circular of the Minister of Education and Culture Numbers 2 and 3 of 2020 requires that the entire teaching and learning process be carried out online. Not all elements of society can accept online learning patterns as a medium for transforming knowledge due to the availability of infrastructure to the characteristics of the community itself. This study aims to explain implementing online learning with the adaptation pattern proposed by Robert Merton. The research design used is a literature review. Articles are collected using the Science and Technology Index (Sinta) link, Garba Reference Digital (Garuda), Ministry of Religious Affairs Reference (Moraref), Indonesian Scientific Repository (Neliti) The Preprint Server of Indonesia (RINarxiv). The time range used is 2011-2021. Based on the results of the study and analysis of the articles collected, it was found that the pattern of adaptation carried out by educators and students is the antithesis of policies issued by the government. The pattern of adaptation carried out by the community is based on the resources and characteristics they have.